Glutaminolysis dynamics during astrocytoma progression correlates with tumor aggressiveness - Moreira Franco, Yollanda E. (Cancer Metab, 2021)
BACKGROUND: Glioblastoma is the most frequent and high-grade adult malignant central nervous system tumor. The prognosis is still poor despite the use of combined therapy involving maximal surgical resection, radiotherapy, and chemotherapy. Metabolic reprogramming currently is recognized as one of the hallmarks of cancer. Glutamine metabolism through glutaminolysis has been associated with tumor cell maintenance and survival, and with antioxidative stress through glutathione (GSH) synthesis. METHODS: In the present study, we analyzed the glutaminolysis-related gene expression levels in our cohort of 153 astrocytomas of different malignant grades and 22 non-neoplastic brain samples through qRT-PCR. Additionally, we investigated the protein expression profile of the key regulator of glutaminolysis (GLS), glutamate dehydrogenase (GLUD1), and glutamate pyruvate transaminase (GPT2) in these samples. We also investigated the glutathione synthase (GS) protein profile and the GSH levels in different grades of astrocytomas. The differential gene expressions were validated in silico on the TCGA database. RESULTS: We found an increase of glutaminase isoform 2 gene (GLSiso2) expression in all grades of astrocytoma compared to non-neoplastic brain tissue, with a gradual expression increment in parallel to malignancy. Genes coding for GLUD1 and GPT2 expression levels varied according to the grade of malignancy, being downregulated in glioblastoma, and upregulated in lower grades of astrocytoma (AGII–AGIII). Significant low GLUD1 and GPT2 protein levels were observed in the mesenchymal subtype of GBM. CONCLUSIONS: In glioblastoma, particularly in the mesenchymal subtype, the downregulation of both genes and proteins (GLUD1 and GPT2) increases the source of glutamate for GSH synthesis and enhances tumor cell fitness due to increased antioxidative capacity. In contrast, in lower-grade astrocytoma, mainly in those harboring the IDH1 mutation, the gene expression profile indicates that tumor cells might be sensitized to oxidative stress due to reduced GSH synthesis. The measurement of GLUD1 and GPT2 metabolic substrates, ammonia, and alanine, by noninvasive MR spectroscopy, may potentially allow the identification of IDH1(mut) AGII and AGIII progression towards secondary GBM. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40170-021-00255-8.